Limit on the fermion masses in technicolor models - Doff, A. [UNESP]; Natale, A. A. [UNESP] (American Physical Society (APS), 2003)
Recently it has been pointed out that no limits can be put on the scale of fermion mass generation (M) in technicolor models, because the relation between the fermion masses (mf) and M depends on the dimensionality of the interaction responsible for generating the fermion mass. Depending on this dimensionality it may happen that mf does not depend on M at all. We show that exactly in this case Mf may reach its largest value, which is almost saturated by the top quark mass. We make a few comments on the question of how large a dynamically generated fermion mass can be. © 2003 The American Physical Society.